The carbon sink balance and weather conditions in Rio de Janeiro city - Paim, Juliana Rodrigues (2024)
This study focuses on carbon balance and the role of vegetation and soils on urban fluxes of CO2. The goal is to evaluate the spatio-temporal variability of the Net Ecosystem Exchange (NEE) and its link with weather conditions in Rio de Janeiro from 2016 to 2020. The empiric-biogenic model was used to estimate the hourly flux of NEE at a 300 meter resolution, using remote sensing data, meteorological variables, and a set of coefficients. The results revealed that there is greater absorption of CO2 in elevated vegetation fractions (80-100%) with a maximum NEE of -1.6 gCO2 m2 hour-1, and lower absorption in urbanized areas with a minimum NEE of -0.6 gCO2 m2 hour-1. The NEE value totals varied daily and seasonally as a function of variation in air temperature and rainfall. By nighttime, the respiration of plants and soils emitted CO2 with a mean of 1.8 tCO2 hour-1, and by daytime, the photosynthesis captured up to -6 tCO2 hour-1. The larger NEE values (-1.800 tCO2) were recorded in summer and the lower NEE (200 tCO2) in winter. The findings of this study contribute to promotion of adaptation and mitigation strategies related to the climate change in the city, taking into account the role of green areas on carbon balance.